2021
DOI: 10.3390/molecules26164787
|View full text |Cite
|
Sign up to set email alerts
|

Lichen-Derived Depsides and Depsidones Modulate the Nrf2, NF-κB and STAT3 Signaling Pathways in Colorectal Cancer Cells

Abstract: The study aimed to evaluate the possible modulation of Nrf2, NF-ĸB and STAT3 signaling pathways in the colorectal cancer (CRC) cells line DLD-1 and HCT116 by secondary metabolites of lichens. An attempt was made to indicate the most promising targets in these signaling pathways. Attention was also paid to the effects of the compounds tested on CRC cells using anakoinosis—that is, simultaneous analysis of several signaling pathways. The effects of the tested natural compounds on the activity of selected transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It was suggested that it might suppress RhoGTPase activity and influence AP‐1, Wnt, and STAT signalling to inhibit lung cancer cell motility and carcinogenesis [32] . A recent study has shown that salazinic acid modulates the Nrf2, NF‐κB, and STAT3 pathways in colorectal cancer [33] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that it might suppress RhoGTPase activity and influence AP‐1, Wnt, and STAT signalling to inhibit lung cancer cell motility and carcinogenesis [32] . A recent study has shown that salazinic acid modulates the Nrf2, NF‐κB, and STAT3 pathways in colorectal cancer [33] …”
Section: Resultsmentioning
confidence: 99%
“…[32] A recent study has shown that salazinic acid modulates the Nrf2, NF-kB, and STAT3 pathways in colorectal cancer. [33] This is the first study in which Molecular docking experiments were carried out to determine the binding orientation of atranorin and salazinic acid to ERα, EGFR, mTOR, and PgR to estimate the stable binding conformation and binding affinity of the lichen compounds with proteins. Among the two lichen metabolites screened, atranorin exhibited docking energy values above À 5 Kcal/mol for receptor ERα, mTOR, and PgR.…”
Section: Cytotoxic Activity and Molecular Dockingmentioning
confidence: 99%
“…Our previous studies revealed that lichen secondary metabolites, especially caperatic acid and physodic acid, exert anticancer properties, inhibiting Wnt/β-catenin pathway in colorectal cancer cells [ 15 , 37 ]. Moreover, in a study by Zhou et al, atranorin was found to suppress β-catenin-mediated TOPFLASH activity by inhibiting the nuclear import of β-catenin and downregulating β-catenin/LEF and c-jun/AP-1 downstream target genes such as CD44 , CCND1 , and c-MYC in lung cancer cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“… 21 Although the STAT3 pathway is regulated by various signaling mechanisms, STAT3 is stimulated by a variety of stimuli, including stress and cytokines. 22 Communication between cancer and inflammatory cells is highly dependent on STAT3 activation and interaction. 23 …”
Section: Introductionmentioning
confidence: 99%